Frequency and Factors Leading to Non-Adherence to SGLT-2 Inhibitors in Patients with Ischemic Heart Disease - Saleem, Atta ur Rehman URF Saleem; Khan, Navedullah; Buriro, Gulzar Ali; Kumar, Mukesh; Amin Ullah,; Jibran ul Haq,; Hassan Ali, Hassan Ali (Indus Journal of Bioscience Research, 2024)
Objective: To evaluate the frequency of non-adherence to sodium-glucose cotransporter-2 (SGLT-2) inhibitors in patients with ischemic heart disease (IHD) and identify factors contributing to non-adherence at National Institute of Cardiovascular Diseases Karachi, Pakistan. Methodology: A prospective descriptive study was conducted on 171 IHD patients prescribed SGLT-2 inhibitors at the National Institute of Cardiovascular Diseases, Karachi. Adherence was assessed using the MMAS-8© scoring system, categorizing patients into high adherence (score = 8), medium adherence (score 6–7), and low-adherence (score < 6), we will take a score of